Heat stress and evisceration caused lipid metabolism and neural transduction changes in sea cucumber: Evidence from metabolomics. (September 2022) - Huo, Da; Su, Fang; Cui, Wei; Liu, Shilin; Zhang, Libin; Yang, Hongsheng; Sun, Lina
Abstract: When encountering adverse environmental conditions, some holothurians can eject their internal organs in a process called evisceration. As global warming intensified, eviscerated and intact sea cucumbers both experience heat stress, but how they performed was uncertain. We constructed 24 metabolomics profiles to reveal the metabolite changes of eviscerated and intact sea cucumbers under normal and high temperature conditions, respectively. Carboxylic acids and fatty acyls were the most abundant metabolic categories in evisceration and heat stress treatments, respectively. Neural transduction was involved in sea cucumber evisceration and stress response, and the commonly enriched pathway was "neuroactive ligand-receptor interaction". Lipid metabolism in eviscerated sea cucumbers differed from those of intact individuals and was more seriously affected by heat stress. Choline is a key metabolite for revealing the evisceration mechanism. Our results contribute to understanding the mechanisms of evisceration in sea cucumbers, and how sea cucumbers might respond to increasingly warming ocean conditions. Graphical abstract: Unlabelled Image Highlights: The metabolomics of eviscerated and intact sea cucumbers varies with temperature. Carboxylic acids and fatty acyls are respectively richest in eviscerated and stressed treatments. Evisceration and stress responses of sea cucumbers may involve neural transduction. Lipid metabolism was depressed in evisceration and heat stress treatments. Choline is a significant metabolite involved in sea cucumber evisceration.